2001
DOI: 10.1097/00001648-200109000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Heart Defects, Maternal Febrile Illness, and Multivitamin Use: A Population-Based Study

Abstract: We assessed the relation between febrile illness during pregnancy and cardiac defects in the offspring in a population-based case-control study in metropolitan Atlanta. Case infants (905) with cardiac defects were actively ascertained from multiple sources. Control infants (3,029) were infants without birth defects who were selected from birth certificates by stratified random sampling. We compared those whose mothers reported febrile illness from 1 month before pregnancy through the third month of pregnancy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
3
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 35 publications
7
86
3
2
Order By: Relevance
“…61 More recent studies suggest that other maternal febrile illnesses during the first trimester of pregnancy also may be associated with an increased risk for certain heart defects. 6,15,62,63 Mothers reporting any febrile illnesses during the first trimester of pregnancy have a 2-fold-higher risk of offspring with any heart defect in these studies. 6,15 Specific groups of defects that have been shown to be associated with maternal febrile illness include pulmonic stenosis, 6 all right-sided obstructive defects, 15 tricuspid atresia, 6,15 coarctation of the aorta, 15 all left-sided obstructive defects, 15 conotruncal defects, and VSDs.…”
Section: Rubella Febrile Illnesses and Influenzamentioning
confidence: 81%
See 2 more Smart Citations
“…61 More recent studies suggest that other maternal febrile illnesses during the first trimester of pregnancy also may be associated with an increased risk for certain heart defects. 6,15,62,63 Mothers reporting any febrile illnesses during the first trimester of pregnancy have a 2-fold-higher risk of offspring with any heart defect in these studies. 6,15 Specific groups of defects that have been shown to be associated with maternal febrile illness include pulmonic stenosis, 6 all right-sided obstructive defects, 15 tricuspid atresia, 6,15 coarctation of the aorta, 15 all left-sided obstructive defects, 15 conotruncal defects, and VSDs.…”
Section: Rubella Febrile Illnesses and Influenzamentioning
confidence: 81%
“…6,15,62,63 Mothers reporting any febrile illnesses during the first trimester of pregnancy have a 2-fold-higher risk of offspring with any heart defect in these studies. 6,15 Specific groups of defects that have been shown to be associated with maternal febrile illness include pulmonic stenosis, 6 all right-sided obstructive defects, 15 tricuspid atresia, 6,15 coarctation of the aorta, 15 all left-sided obstructive defects, 15 conotruncal defects, and VSDs. 15 A case-control study in California found an association of maternal fever with conotruncal defects among offspring born to mothers who did not use multivitamins.…”
Section: Rubella Febrile Illnesses and Influenzamentioning
confidence: 81%
See 1 more Smart Citation
“…Few studies provide race-specific prevalence estimates for types of CHD and results are inconclusive [3,[6][7][8][9][10][11]. Some studies report excess risk of specific types of CHDs for Whites compared to Blacks and very few studies have reported risk of specific types of CHD for Hispanics.…”
Section: Introductionmentioning
confidence: 99%
“…Среди ВПС у детей, рожденных от матерей, перенес-ших острый инфекционный процесс во время беременно-сти, в большей степени распространены пороки клапана легочной артерии, синдромы с обструкцией правых или левых камер сердца, пороки развития трикуспидально-го клапана, коарктация аорты, ДМЖП [36]. Инфекции мочевыводящих путей у беременной женщины чаще были связаны с ВПС, приводящими к обструкции правых камер сердца; и, наоборот, респираторные инфекции в большинстве случаев протекали без формирования ВПС [37].…”
Section: заболевания беременной женщиныunclassified